Tingkat Kepemimpinan Efektif Pada Mahasiswa Program Studi Aakuntansi Angkatan 2017 Universitas Informatika dan Bisnis Indonesia - Rachmawati Windyaningrum (ArtComm, 2020)
Leadership becomes an important value that must be possessed by every student. Students as agents of change, are not only able to provide critical thinking, but must also be accompanied by a responsible attitude, able to achieve goals, and overcome changes and make the right decisions. The University of Informatics and Business of Indonesia (UNIBI) has the uniqueness to equip students as prospective scholars who are leaders and think globally through the provision of global leadership courses. This study aims to measure the level of effective leadership of UNIBI Accounting Study Program students based on aspects of basic style of leadership and effective style. This research method uses a quantitative approach with the survey method of leadership measurement of William J. Reddin, to 15 students of the 2017 Accounting Study Program who are the research population. The population was chosen based on the sampling quota, which is the total number of students taking Global Leadership classes. The results of research based on aspects of basic style leadership found 66.6% of students have a high orientation to the task or job and high on relationships. Aspects of effective leadership as many as 73% of students have more effective leadership skills. Conclusions the basic level of student leadership is high and effective leadership is very high.